STRUCTURAL ANALYSIS OF COPING WITH PRE-EXAMS ANXIETY AND UNCERTAINTY (COPEAU) IN PERUVIAN COLLEGE STUDENTS - Dominguez-Lara, Sergio Alexis (2016)
The objective of this research was analyze the internal structure of Coping with Pre-Exam Anxiety and Uncertainty (COPEAU) in Peruvian college students from a private institution. Participated 312 psychology students (227 women) from from the first to sixth term, with age between 16 and 49 (M = 20.54; SD = 4.29). Using the structural equation modeling, five models were assessed, among which the four oblique factor model shows greater theoretical and empirical coherence.. Also, the reliability indices were appropriate. The practical implications of the results in the context of a broader theory of coping with stress were discussed, as well as the relevance of some procedures in analytical studies-factorial approach.